Levels of Cortisol and Inflammatory Cytokines after The Induction of Various Sleep Deprivation Stress Models in Male Wistar Rats - Fitranto Arjadi; Sindhu Wisesa; Nor Sri Inayani; Prasetyo Tri Kuncoro; Catharina Widiartini (Universitas Jenderal Soedirman, 2022)
Sleep deprivation (SD) can modulate the production of various cytokines, including pro-inflammatory cytokines such as IL-6, TNF-α, and IFN-γ, and anti-inflammatory cytokines such as IL-10. Paradoxical sleep deprivation (PSD) increases the risk of inflammation but can be relieved by sleep recovery (SR). This study aimed to determine the differences in levels of cortisol and inflammatory cytokines (IL-6, IL-10, TNF-α, dan IFN-γ) in male Wistar rats (Rattus norvegicus) after induction of various sleep deprivation stress models. Twenty-five of male Wistar rats were randomly divided into five groups: control, PSD (20 hours of SD/day for five days), Total Sleep Deprivation or TSD (24 hours of SD/day for five days), PSD+SR (PSD followed by SR), and TSD+SR (TSD followed by SR). The plasma cortisol levels were measured with ELISA, and inflammatory cytokine levels were measured with immunoassay and calculated with fold change. Mean cortisol levels were significantly increased in treatment groups compared to the control group (p=0.029). Multivariate analysis showed no statistically significant difference in inflammatory cytokine levels of IL-6 (p=0.658), IL-10 (p=0.065), TNF-α (p=0.399), and IFN-γ (p=0.283) in all groups. In conclusion, various sleep deprivation stress models affect cortisol levels but not inflammatory cytokine levels of IL-6, IL-10, TNF-α, and IFN-γ among male Wistar rats.